Hygienic substantiation of calculating models for predicting toxicity of different classes insecticides (first part). - A. M. Antonenko; O. P. Vavrinevych; S. T. Omelchuk; B. I. Shpak (Medičnì Perspektivi)
This work is the first part of our study to develop alternative experimental mathematic models for predicting toxicity of insecticides. In the first stage, calculations will be carried out and the most reliable models will be proposed. In the second – a statistical analysis and comparative estimation of the toxicometric parameters obtained experimentally and calculated according to the proposed equations. The purpose of the research is the scientific substantiation of the calculation models for predicting toxicity of insecticides of different classes. Data on the physico-chemical properties and toxicometry parameters of fungicides are taken from the PPDB pesticides database. Insecticides of such chemical classes as derivatives of tetram and tetronic acids, benzoylureas, carbamates, neonicotinoids, pyrethroids, organophosphorus compounds, avermectins were selected for analysis. It has been established that there is a significant positive correlation between NO(A)EL in the chronic experiment of all insecticides, the median lethal doses at oral administration (LD50 per os) of pyrithoids and neonicotinoids, and the molecular weight (at p<0.05). There is a significant negative correlation between the toxicometry parameters of all insecticides and their individual groups (pyrithoids, neonicotinoids, organophosphorus compounds) and melting temperature and the octanol-water partition coefficient, log Po/w (at p<0.05). It is proved that the proposed calculation models for predicting insecticide hazards are adequate according to Fisher's criterion, and the coefficients of regression equations are reliable according to Student's criterion (p<0,05).